Anti-VEGF Effect of Bioactive Indolic Compounds and Hydroxytyrosol Metabolites - Marta Gallardo-Fernández; Ana B. Cerezo; Ruth Hornedo-Ortega; Ana M. Troncoso; M. Carmen Garcia-Parrilla (Foods, 2022)
Angiogenesis is a key process involved in both cancer and cardiovascular diseases, the vascular endothelial growth factor (VEGF) and its VEGF receptor-2 (VEGFR-2) being the main triggers. The aim of this study was to determine the molecular mechanism underlying the potent inhibition of VEGF signaling by hydroxytyrosol (HT) metabolites and indolic compounds and establish a relation between their structure and bioactivity. Experiments involved the evaluation of their potential to inhibit VEGF on human umbilical vein endothelial cells (HUVECs) by ELISA assay and their subsequent effect on the downstream signaling pathway (PLCγ1, Akt, and endothelial nitric oxide synthetase (eNOS)) by Western blot. Respectively, 3,4-dihydroxyphenylacetaldehyde (DOPAL) (100 µM) and indole pyruvic acid (IPy) (1 mM) were capable of inhibiting VEGFR-2 activation with an IC50 value of 119 µM and 1.037 mM. The anti-angiogenic effect of DOPAL and IPy is mediated via PLCγ1. Additionally, DOPAL significantly increases eNOS phosphorylation, while IPy maintained it. These data provide for the first time evidence of the anti-angiogenic effect of DOPAL and IPy for future use as potential bioactive food ingredients.